Prevalence Of Allergic Fungal Rhinosinusitis Among Patients Having Nasal Polyposis - Malik, Tehreem Ramzan; Zamurrad Malik, Kamran; Ali, Muhammad; Tahir, Muhammad; Akram, Junaid; Tahir, Aaiza (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the prevalence of allergic fungal rhinosinusitis among patients with nasal polyps and associate it with risk factors Methods: This cross-sectional study design was conducted at the ENT department of Combined Military Hospital Quetta, from January to December 2024. One hundred and sixty-three adult patients presenting with bilateral nasal polyps were enrolled in the study. All the patients underwent functional endoscopic sinus surgery, and the histopathology sample reports were evaluated. Patients were assessed according to the Bent and Kuhn diagnostic criteria for allergic fungal rhinosinusitis, which include the presence of nasal polyps with characteristic double-density CT findings, fungal hyphae on fungal microscopy, and the presence of eosinophilic mucin on histopathology samples, and were labelled as having allergic fungal rhinosinusitis. Results: Out of 163, there were 76 (46.6%) males and 87 (53.4%) females with a mean age of 49.10±9.4 years. Allergic fungal rhinosinusitis was found in 50 (30.7%) of the patients. Females were more commonly found to have allergic fungal rhinosinusitis as compared to males (34.0% vs 66.0%, p=0.032). A higher percentage of patients with allergic fungal rhinosinusitis were found to have a history of allergy (p<0.001), diabetes (p<0.001) and hypertension (p=0.001) as compared to those without allergic fungal rhinosinusitis. Conclusion: The frequency of allergic fungal rhinosinusitis was reported to be 30.7% among patients presenting with nasal polyps, where the mean nasal score was higher among such patients, along with various risk factors, including gender, history of allergy, diabetes and hypertension. Keywords: Nasal polyps, allergic fungal sinusitis, risk factors, allergy, fungal infection